(untitled) (Swiss Medical Weekly, 2014)
Although tissue engineering and cell therapies are becoming realistic approaches for medical therapeutics, it is likely that musculoskeletal applications will be among the first to benefit on a large scale. Cell sources for tissue engineering and cell therapies for tendon pathologies are reviewed with an emphasis on small defect tendon injuries as seen in the hand which could adapt well to injectable cell administration. Specifically, cell sources including tenocytes, tendon sheath fibroblasts, bone marrow or adipose-derived stem cells, amniotic cells, placenta cells and platelet-derivatives have been proposed to enhance tendon regeneration. The associated advantages and disadvantages for these different strategies will be discussed and evolving regulatory requirements for cellular therapies will also be addressed. Human progenitor tenocytes, along with their clinical cell banking potential, will be presented as an alternative cell source solution. Similar cell banking techniques have already been described with other progenitor cell types in the 1950’s for vaccine production, and these “old” cell types incite potentially interesting therapeutic options that could be improved with modern innovation for tendon regeneration and repair.